Influence of environmental conditions on students' learning processes: A systematic review. (1st March 2023) - Villarreal Arroyo, Yesica Paola; Peñabaena-Niebles, Rita; Berdugo Correa, Carmen
Abstract: Environmental comfort directly influences student learning. Thus, to strengthen this process, it is possible to identify school buildings' most favourable environmental conditions and consider them when designing and constructing infrastructure for educational purposes. This has motivated research to determine how the environmental factors of school buildings influence the teaching-learning processes. This study aims to systematically organise, classify, categorise, and analyse the existing literature on the environmental conditions of classrooms and their influence on students' learning processes. Thus, future researchers will have a helpful guide to define the elements to consider when studying, analysing, and determining the environmental variables in school buildings that favour learning. Consequently, 71 studies classified in a scheme comprising categories designed to ensure an in-depth analysis of the most relevant topics in this area of research were considered. The results present multiple research opportunities in this field of study. The main conclusions are that the countries with the most significant interest in researching this topic are in Europe or Asia, with a common motivation to explore the adaptations necessary for the change in season. In contrast, the study variables of the most significant interest were associated with thermal comfort. Finally, it is concluded that these studies, in most cases, do not measure variables related to learning or identifying a variable of potential study to define environmental conditions.